Efektivitas Dana KIP-K Dalam Mendukung Pengeluaran Mahasiswa Angkatan 2023 Di Kampus Negeri Palangka Raya - Marsa Adelia Marsa; Wirna Lisa; Septia Septia; Bhayu Rhama; Subhan Ilham Thareq (Universitas Mbojo Bima, 2025)
Abstract. This research aims to examine the influence of the Indonesia Smart College Card (KIP-K) fund effectiveness on student expenditures among the 2023 cohort at a State University in Palangka Raya. The study employs a quantitative method using simple linear regression analysis. The findings reveal that the effectiveness of the KIP-K fund has a positive and significant impact on student expenditures, as indicated by a significance value of < 0.001 (< 0.05) and a t-value of 5.927, which exceeds the t-table value of 1.989. The regression coefficient of 0.842 suggests that a 1% increase in the effectiveness of the KIP-K fund corresponds to a 0.842% rise in student expenditures. Furthermore, the R Square value of 0.366 implies that 36.6% of the variation in student expenditures is explained by the effectiveness of the KIP-K fund, while the remaining 63.4% is attributed to other factors, such as family support, part-time employment, and lifestyle. Despite its statistically significant impact, the implementation of the KIP-K program still encounters several obstacles, including delays in fund disbursement, insufficient financial support, and limited financial literacy among recipients. Hence, improvements in the punctuality of fund distribution, transparency in management, and financial guidance for students are essential to enhance the program’s overall effectiveness and sustainability. Abstark. Penelitian ini bertujuan untuk menelaah pengaruh efektivitas penggunaan dana Kartu Indonesia Pintar Kuliah (KIP-K) terhadap tingkat pengeluaran mahasiswa angkatan 2023 di Kampus Negeri Palangka Raya. Metode yang digunakan adalah pendekatan kuantitatif dengan teknik analisis regresi linear sederhana. Hasil penelitian memperlihatkan bahwa efektivitas dana KIP-K berpengaruh positif dan signifikan terhadap pengeluaran mahasiswa. Hal ini dibuktikan dengan nilai signifikansi < 0,001 (< 0,05) serta nilai t hitung 5,927 yang lebih besar dari t tabel 1,989. Koefisien regresi sebesar 0,842 menunjukkan bahwa setiap peningkatan efektivitas dana KIP-K sebesar 1% akan meningkatkan pengeluaran mahasiswa sebesar 0,842%. Nilai R Square sebesar 0,366 menandakan bahwa 36,6% variasi dalam pengeluaran mahasiswa dapat dijelaskan oleh efektivitas dana KIP-K, sementara sisanya dipengaruhi oleh faktor lain seperti dukungan keluarga, pekerjaan sampingan, dan gaya hidup. Meskipun secara statistik menunjukkan hasil yang positif, pelaksanaan program KIP-K masih menemui sejumlah kendala, di antaranya keterlambatan pencairan dana, jumlah bantuan yang belum sepenuhnya mencukupi, serta rendahnya kemampuan mahasiswa dalam mengelola keuangan. Oleh sebab itu, dibutuhkan perbaikan dalam hal ketepatan waktu pencairan, transparansi penyaluran, serta pendampingan keuangan bagi penerima agar implementasi program KIP-K dapat berlangsung lebih efektif dan berkelanjutan.